Novel in-situ preparation of nano sized Ni (0) catalyst for depolymerization of lignin-rich waste from industrial biorefinery. (June 2020) - Carrozza, Chiara F.; Leonardi, Gabriella; Vasso, Michele; Gelfi, Cecilia; Serafini, Andrea; Gambarotti, Cristian; Citterio, Attilio; Sebastiano, Roberto
Abstract: Lignin-rich waste are valuable sources of chemicals and other materials but the depolymerisation processes are still unworkable on industrial scale. One of the problems ongoing is the catalyst preparation which often requires laborious and time-consuming processes. In this paper, a first example of easy preparation of in-situ Ni(0) nano sized catalyst for lignin-rich industrial waste hydrogenolysis is reported. Ni(0) particles were produced by reduction of Ni(II) acetate dissolved in alcoholic suspension of lignin. Soda lignin was isolated from the solid stream of a second generation bioethanol industrial plant and was depolymerized to low molecular weight chemicals by Ni(0) and/or Pd/C in alcoholic media. In 1, 2-propandiol at 210 °C, up to 70% of starting material was converted into soluble compounds with an overall yield of monolignol derivatives of about 18%. The remaining material is constituted by lignin fragments with molecular weight between 400 and 1400 Da. The oligomers formation and distribution was discussed. Highlights: In-situ catalyst preparation for biomass treatments Lignin as nano sized metal particles maker Lignin waste valorisation from bioethanol industrial plant Reduced lignin oligomers for composite materials